Antibacterial activity of fractions from papaya seeds (Carica papaya L.) extract against Escherichia coli and Salmonella typhi and the contributing compounds - Devi Nisa Hidayati; Nurul Hidayati; Esa Evinda; Nur Rahayu Fitriana; Awal Prichatin Kusumadewi (Universitas Ahmad Dahlan, 2019)
Papaya (Carica papaya L.) seed has been reported to have antibacterial activity against Escherichia coli and Salmonella typhi. It contains compounds like alkaloids, flavonoids, saponins, and terpenoids. This study aimed to determine the antibacterial activity of fractions from the ethanolic extract of papaya seed against Escherichia coli and Salmonella typhi and identify the specific compounds that contribute to their efficacy. Papaya seeds were extracted through maceration with 70% ethanol solvent, and the extracts were subjected to fractionation with n-hexane, ethyl acetate, and water solvents and followed by a diffusion method to examine the antibacterial activity of both extracts and fractions. Fractions with a series of concentrations were used, namely 10-50% (n-hexane and ethyl acetate fractions) and 100-500% (water fraction). The compounds of the ethanolic extract and its fractions were identified with phytochemical screening. The results showed that the n-hexane and water fractions exhibited antibacterial activity against Escherichia coli when applied at a minimum of 10% and 100% concentration, respectively, but not against Salmonella typhi. Meanwhile, starting from 10% concentration, the ethyl acetate fraction was able to prevent the growth of both Escherichia coli and Salmonella typhi. The compound detection tests revealed that the n-hexane fraction contained alkaloids and terpenoids, the ethyl acetate fraction had alkaloids, flavonoids, and saponins, and the water fraction comprised flavonoids and saponins.Â